EVALUASI KERUSAKAN BETON DAN METODE PERBAIKAN - F.Eddy Poerwodihardjo; Dwi Istiningsih (Fakultas Teknik, Universitas Wijayakusuma Purwokerto, 2020)
Massive use of concrete in building construction requires an evaluation of the quality and implementation of work so that construction can function according to the age of the plan. It aims to determine the ability of a structure that is analyzed systematically, including the dimensions of geometry, materials, and current structural conditions. Concrete construction that is strong and durable requires the selection of quality materials and the process of implementing a perfect concrete. If damage occurs, it is necessary to carry out continuous evaluations and repair concrete as well as structural reinforcement. So that the concrete construction function returns to good performance. Damages that often occur include: porous, disintegration and weathering of materials, corrosion of steel reinforcement, cracks on concrete plates, honeycomb / hollow concrete and uneven concrete or bulging on the surface. Methods of improvement that can be done include: chipping and concreting, strengthening, shot concrete, grouting, jacketing and patching or sealing. The method of repairs carried out must be in accordance with the evaluation of damage and cost factors. Keywords: concrete, damage, repair ABSTRAKPenggunaan beton pada konstruksi bangunan secara masif memerlukan evaluasi mutu dan pelaksanaan pekerjaan agar konstruksi dapat berfungsi sesuai umur rencana. Hal ini bertujuan untuk mengetahui kemampuan dari sebuah struktur yang dianalisa secara sistematik, meliputi dimensi geometri, bahan material, dan kondisi struktur terkini. Konstruksi beton yang kuat dan awet memerlukan pemilihan bahan yang bermutu dan proses pelaksanaan beton yang sempurna. Bila terjadi kerusakan, perlu diadakan evaluasi secara terus menerus dan dilakukan perbaikan beton maupun perkuatan struktur. Sehingga fungsi konstruksi beton kembali pada performa yang baik. Kerusakan yang sering terjadi antara lain : keropos, disintegrasi dan pelapukan bahan, korosi tulangan baja, retak pada plat dak beton, honeycomb/beton berongga dan beton yang tidak rata atau menggembung pada permukaannya. Metode perbaikan yang dapat dilakukan antara lain adalah : chipping and concreting, strengthening, shot crete, grouting, jacketing dan patching or sealing. Metode perbaikan yang dilakukan harus sesuai dengan evaluasi kerusakan yang terjadi dan faktor biaya. Kata kunci : beton, kerusakan, perbaikan